Potentials and weaknesses of the extension project “Cow’s milk protein allergy (CMPA) and care with children”, in the post-pandemic period: an experience report (Research, Society and Development, 2023)
Milk Protein Allergy (CMPA) is the food allergy that most affects children, triggering a varied immune response that causes a series of symptoms, such as diarrhea and oral allergy syndrome (OAS), deeply affecting the quality of life of the patient and his family. In parallel to this, the development of academic extension actions is fundamental to promote a continuous work of health education for the community, inserting the student in his future workplace, offering an essential experience for personal and intellectual development. This study aims to report the experience of medical students from a private medical school in João Pessoa/PB with the Extension Project "CMPA and Child Care", describing the present and virtual activities performed during the time of participation in the project. During the experience, it was possible to observe that people's knowledge about the disease is still quite scarce, arousing a lot of curiosity during educational activities in waiting rooms. On the other hand, it was noted that there was no considerable interest from health professionals to participate in training workshops about CMPA, hindering the dissemination of knowledge. Finally, we conclude that there are still barriers to the dissemination of information on CMPA, but also that digital media have proven to be excellent tools to reach a larger target audience and with greater effectiveness.